ChemInform Abstract: Convenient One‐Pot Synthesis of N3‐Substituted Pyrido[2, 3‐d]‐, Pyrido[3, 4‐d]‐, Pyrido[4, 3‐d]‐pyrimidin‐4(3H)‐ones, and Quinazolin‐4(3H)‐ones Analogues. Issue 42 (1st October 2013) - Deau, Emmanuel; Hedou, Damien; Chosson, Elizabeth; Levacher, Vincent; Besson, Thierry
Abstract The process allows the conversion of anthranilic acids as well as aminonicotinic acid and derivatives into the required heteroaromatic compounds.